Improving vitamin D content in pork meat by UVB biofortification. (May 2023) - Neill, H.R.; Gill, C.I.R.; McDonald, E.J.; McMurray, R.; McRoberts, W.C.; Loy, R.; White, A.; Little, R.; Muns, R.; Rosbotham, E.J.; O'Neill, U.; Smyth, S.; et al.
Abstract: Vitamin D deficiency is prevalent worldwide and identification of alternative food-based strategies are urgently warranted. In two studies, 12-week old crossbred pigs (Duroc x (Large White x Landrace)) were exposed daily to narrowband UVB radiation for ∼10 weeks or control (no UVB exposure) until slaughter. In Study 1 ( n  = 48), pigs were exposed to UVB for 2 min and in Study 2 ( n  = 20), this duration was tripled to 6 min. All pigs were fed the maximum permitted 2000 IU vitamin D3 /kg feed. Loin meat was cooked prior to vitamin D LC-MS/MS analysis. In Study 1, pork loin vitamin D3 did not differ between groups. Study 2 provided longer UVB exposure time and resulted in significantly higher loin vitamin D3 (11.97 vs. 6.03 μg/kg), 25(OH)D3 (2.09 vs. 1.65 μg/kg) and total vitamin D activity (22.88 vs. 14.50 μg/kg) concentrations, compared to control ( P <  0.05). Pigs remained healthy during both studies and developed no signs of erythema. Biofortification by UVB radiation provides an effective strategy to further safely increase the naturally occurring vitamin D content of pork loin, alongside feed supplementation. Highlights: Food-based strategies are warranted to address suboptimal vitamin D intakes. Daily UVB exposure over 9 weeks doubled vitamin D3 concentrations in pork loin. UV pigs which stood more during exposure had higher loin vitamin D3 concentrations.